Entwicklungsforschung aus einer handlungstheoretischen Perspektive: Was Design Based Research von Hannah Arendt lernen könnte. - Jahn, Dirk (Educational Design Research, 2017)
This contribution analyses the design based research (DBR) process from perspective of action theory and discusses its epistemological and methodological consequences. For this purpose the concept of action is scrutinised, following a particular line of thinking proposed by the philosopher Hanna Arendt (1996). The overall aim of the text is to outline a potential and possibly important perspective on design based research, to strengthen DBR as a distinct and adequate research approach, and to bring to mind its original and pragmatic concern: novelty, usefulness and sustainable innovation.
Keywords: Entwickeln als wissenschaftlicher Akt Handlungstheorie im Kontext Entwicklungsforschung Wissenschaftliche Geltungsansprüche aus handlungstheoretischer Perspektive